Corrosion inhibition of aluminum current collector with molybdate conversion coating in commercial LiPF6-esters electrolytes. (September 2021) - Yang, Shanglin; Li, Songmei; Meng, Yanbing; Yu, Mei; Liu, Jianhua; Li, Bin
Highlights: A molybdate conversion treatment was performed on aluminum current collector (AlCC) in the LiPF6 -esters electrolyte of LIB. The obtained molybdate conversion coating (MCC) not only isolates organic electrolytes but also acts as a conductive film. Scanning electrochemical microscope confirmed that the corrosion type of Al current collector is pitting corrosion. MCC-AlCC has considerable cycling stability at high voltage of 4.5 V in Li||NMC333 cell. Abstract: A molybdate conversion coating (MCC) is developed to circumvent aluminum current collector (AlCC) corrosion in commercial LiPF6 -esters electrolytes. The obtained MCC exhibits compact structure and good combination with AlCC matrix. Electrochemical tests show that MCC reduces the corrosion current density by an order of magnitude. Furthermore, in Li||NMC333 cells, the capacity retention of the cell with MCC-AlCC cathode is 75.6 % at 4.5 V high voltage, while that of control cell is only 7.2 %. The anticorrosion mechanism could be contributed to the stable artificial passivation layer which prevents HF erosion and the depth expansion of pitting corrosion.